Effects of pre- and post-veraison cluster thinning on Montepulciano and Cabernet Franc grape varieties in southern Brazil highlands (Revista de Ciências Agroveterinárias, 2018)
The objective of this study was to evaluate the effects of pre- and post-veraison cluster thinning on the physicochemical characteristics of Montepulciano and Cabernet Franc grape varieties grown in regions 900 m above sea level (ASL) in Santa Catarina, southern region of Brazil. The experiment was conducted in two commercial vineyards, Montepulciano vineyard located at 28º12'58''S, 50º06'45''W, 1,185 m ASL during the 2007, 2008 and 2009 vintages; and Cabernet Franc vineyard located at 28°15'20"S, 49°56'60"W, 1,284 m ASL, during the 2010 and 2011 vintages. Treatments consisted on cluster thinning at three distinct moments for both varieties: during veraison, about 15 days pre-veraison and 15 days post-veraison. For Montepulciano, when cluster thinning is performed post-veraison, there is a reduction in cluster mass and a slight reduction on the acidity of grapes. For Cabernet Franc, when cluster thinning is performed during veraison, there is an increase in total soluble solids of grapes. In general, cluster thinning is recommended two weeks pre- or post-veraison for Montepulciano and Cabernet Franc wine grapes produced in southern Brazilian highlands.
Keywords: Vitis vinifera L.; management; ripening; total polyphenols; altitude wines